THE PLACE OF AUGMENTED VIRTUALITY IN THE SYSTEM OF IMMERSIVE EDUCATIONAL TECHNOLOGIES - Bidaibekov, Е.Ы.; Grinshkun, А.В.; Н.Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article is devoted to the analysis of existing ways to improve the effectiveness of the educational process due to the visibility and interactivity of learning tools. The authors identified two main types of funds – real and virtual objects. Real ones allow you to study the physical properties of an object most fully, as well as develop working skills, and virtual ones demonstrate what is not available in mass education. Immersive technologies allow us to combine the advantages of both approaches in many ways. At the same time, augmented virtuality technology allows you to immerse the student in an inaccessible environment while maintaining physical feedback, as well as the ability to develop working skills. At the same time, the technology is practically not used in mass education, unlike augmented and virtual reality. For the successful application of such technology, it is necessary to study the methodological support.